ANÁLISE DE CUSTOS PARA OBTENÇÃO DO SELO IPTU VERDE EM EMPREENDIMENTO RESIDENCIAL NA CIDADE DE SALVADOR-BA - Brasileiro, Roberta; Alberte, Elaine; Ventin, Jadi (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
One of the major concerns of construction sector in this day and age is to design products according to sustainability concepts. In 2015, the municipal government of Salvador launched a program of green taxes as a way to encourage sustainable actions and practices in real estate projects in the region. In the program, scores were assigned for sustainable solutions implemented in the project, according to their level of environmental impact. The sum of theses scores would generate progressive discounts in taxes of urban land and territory for the projects final user. This work analyzes the economic impact associated with design decisions to meet the parameters of this municipal environmental certification. The analysis estimates the cost for applying these sustainable adaptations in an advanced project of a typical residential building located in Salvador, Bahia, Brazil, that are needed to achieve this certification. Thus, a comparative budget analysis was carried out between the original project and the adapted project. As a result, it was possible to estimate the return time of 48 years considering only the IPTU discount and it was possible to identify the sustainable solutions that have the best cost-per-score to achieve the certification and the increase of cost per square meter for sustainable residential projects.